Religious Gender in the view of Christianity: Comparatives of the Creation and Patriarchal Structure on Genesis - FAN, Chun-Ming (Journal of Research for Christianity in China (JRCC), 2025)
The Foreword of the Traditional Interpretation: the traditional gender thinking always considers that the male is higher than the female mostly, it just like that the female is a portrayal of the male’s servant. It is believed that men should be the leaders of the social organizations and the women should be under the rule of men to maintain the operational mode among the organization and the society. That promotes the level of rationalization to the women under the jurisdiction of men in many areas under the society. There is also a male-leading atmosphere of consciousness which is encouraged by the religious classics. Most ideology of masculinity is not only among the world religions such as Buddhism, Hinduism, Islam, etc. That can also be seen in the regional religions and contributed to the patriarchal authoritarian system. Second, the Comparison with the Traditional Interpretation: The Hebrew words אָדָ֛ם(people) of “Genesis 2:7-8”, the עֵזֶר(spouse) of “Genesis 2:18-20”, the אִשָּׁה(ribs) of “Genesis 2:21-25”, the pregnancy and being governed of “Genesis 3:8-21”. When such original text is used, different interpretation rules are proposed for the text of the Bible as a different interpretation space for the Biblical religions. The male-dominated of the Bible religions and its classics do not stifle the women’s functions, religious experiences and social status. There are also such records of the women who saving the state and killing the enemy. They are no less inferior to the men during such crisis moment. Through the complete description of the classic, the Bible religions do not blindly place the women under the men purposely. Even if male-dominated ingredients are much more than the women but do not despise, discriminate or devalue the women in the Bible, especially on the matter of their position and status. Third, the Gender System under the Patriarchal Structure: from the perspectives of social politics, education culture and religious experience which each level shapes the different view to the genders. The reason why the feminism rejects the masculine orientation on religions is that the fundamentalism is not adding inspections but also fully recognizes the doctrines and statutes of religions. The patriarchal structure continues to manifest in the scope of religions which having different developments in different religious systems. The development of patriarchal structures on different religions is not the same. The natural phenomenon of the original gender difference turns into a normal consciousness. In the development of religions, it becomes the structure of the constructed thinking and meaning. As a distinct of the society, it is not the essence of being born or given. The gender is indifferent in order to maintain the patriarchal structure and the religious level rationalizes this principle. Fourth, the Conclusion: The gender awareness has become a significant symbol of the present and plays an important part of self-identity. Especially under the circumstance of new religions and globalization, the women may have more patriarchal ideology than before. They can negotiate with more space. The stereotype of the traditional patriarchy may also face the disintegration and change for their dominant position.